2019
DOI: 10.18805/lr-4059
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response of chickpea (Cicer arietinum L.) at early seedling stage under salt stress conditions

Abstract: Screening of chickpea lines for salt tolerance through seed germination and early seedling growth is crucial for their evaluation. Seeds of 30 chickpea genotypes were germinated on a sand bed irrigated with saline (3, 6, 9, 12 dS/m) and control solutions upto 30 days. At the early seedling stage (25-30 days), germination percentage, chlorophyll content, proline, root length, shoot length and seedling dry weight were found to be affected due to salinity. Salt tolerance index (STI) for plant biomass maintained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
4
23
0
Order By: Relevance
“…These toxic ions interfere with the normal physiological processes causing membrane damage, nutrient imbalance, altered levels of growth regulators, enzymatic inhibition and metabolic dysfunction, including photosynthesis which ultimately leads to plant death ( Mahajan and Tuteja, 2005 , Kumar et al, 2018a , Kumar et al, 2019 ). Thus the plant growth is impaired by osmotic stress in a first phase and ionic stress in second phase (accumulation of high concentrations of salts (toxic ions) within the plant which damages cell functions and structure) and finally suppress the yield ( Kumar et al, 2018b , Mann et al, 2019a ). These negative effects include interference of root function in absorbing water, as well as the prevention of physiological and biochemical processes such as uptake of nutrient like Ca ++ , Mg ++ and K + and their assimilation ( Carillo et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…These toxic ions interfere with the normal physiological processes causing membrane damage, nutrient imbalance, altered levels of growth regulators, enzymatic inhibition and metabolic dysfunction, including photosynthesis which ultimately leads to plant death ( Mahajan and Tuteja, 2005 , Kumar et al, 2018a , Kumar et al, 2019 ). Thus the plant growth is impaired by osmotic stress in a first phase and ionic stress in second phase (accumulation of high concentrations of salts (toxic ions) within the plant which damages cell functions and structure) and finally suppress the yield ( Kumar et al, 2018b , Mann et al, 2019a ). These negative effects include interference of root function in absorbing water, as well as the prevention of physiological and biochemical processes such as uptake of nutrient like Ca ++ , Mg ++ and K + and their assimilation ( Carillo et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some legumes plants are more tolerant to a high salt concentration than others e.g., lentils are more tolerant than soybean and chickpea. Recently, few salt tolerant chickpea lines have been identified for survival at early seedling stage in saline soils with EC of irrigation water from 3 to 12 dS/m [15]. Earlier, pea genotypes have been categorized as sensitive, moderately tolerant or tolerant to salinity based on physiological and biochemical expressions of salt tolerance [16].…”
Section: Crops and Saline Soilsmentioning
confidence: 99%
“…The previous studies showed the effects of salinity in root growth and development in the model and common crops (Talukdar, 2011;Hasan et al 2018;Mann et al 2019). Also, there were several reports of the effect of salinity at the germination stage on forage pea (Demirkol et al 2019;Önal Aşçı and Zambi, 2020), however, no previous reports on the seedling root architecture and salinity interactions were found.…”
Section: Introductionmentioning
confidence: 98%